Iron Chelate Improves Rooting in Indole-3-Butyric Acid-Treated Rosemary (Rosmarinus officinalis) Stem Cuttings - Zeinab Izadi; Abdolhossein Rezaei Nejad; Javier Abadía (Agriculture, 2022)
Adventitious root formation in stem cuttings is affected by exogenous and endogenous factors. The study assessed the effect of Fe(III)-EDDHA (ethylenediamine-N,N-bis 2-hydroxyphenyl acetic acid) on the rooting of 4 indol-3-butyric acid (IBA)-treated hardwood cuttings of the aromatic and medicinal species Rosmarinus officinalis. Cuttings treated with 0, 1000, 2000 or 3000 mg L−1 IBA were placed in pots filled with sand:perlite mixture and irrigated daily with nutrient solution pH 5.8, containing 0, 5, 10 or 20 µM Fe(III)-EDDHA. Ten days later, the number of new emerging roots were recorded. After 20 days, leaf photosynthetic pigments and morphological traits, including root number, fresh (FW) and dry weight (DW), shoot FW and DW, mean length of the longest roots, number of new shoots and new growth in old shoots, were measured. Finally, plants were transplanted to pots filled with a sand:soil mixture and survival was measured after 10 days. Results indicate that Fe application promotes root emergence and improves root and shoot biomass, leaf photosynthetic pigment concentrations and survival percentage. This indicates that using low concentrations of Fe(III)-EDDHA (5–20 µM) in the growth medium could be a good management strategy to facilitate the production of vigorous R. officinalis plants from hardwood cuttings.